Airborne protection for staff is associated with reduced hospital-acquired COVID-19 in English NHS trusts. (February 2022) - Lawton, T.; Butler, M.; Peters, C.
Summary: Introduction: The rate of hospital-acquired coronavirus disease 2019 has reduced from 14.3% to 4.2% over the last year, but substantial differences still exist between English National Health Service (NHS) hospital trusts. Methods: This study assessed rates of hospital-acquired infection (HAI), comparing NHS hospital trusts using airborne respiratory protection (e.g. FFP3 masks) for all staff, as a marker of measures to reduce airborne spread, with NHS hospital trusts using mainly droplet precautions (e.g. surgical masks). Results/discussion: The use of respiratory protective equipment was associated with a 33% reduction in the odds of HAI in the Delta wave, and a 21% reduction in the odds of HAI in the Alpha wave ( P <0.00001). It is recommended that all hospitals should prioritize airborne mitigation.